Interactive Learning Multimedia Using Contextual Approach for Students in Fifth Grade of Elementary School - Fauziyah, Syifa'ul; Sudatha, I Gde Wawan; Sudarma, I Komang (Universitas Pendidikan Ganesha, 2024)
There is no learning media that can facilitate learning so that students tend to be passive and have an impact on low student learning outcomes. The purpose of this study is to develop interactive learning multimedia with a contextual approach to improve the learning outcomes of fifth grade elementary school students in science. This study is development research with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The data collection methods used in this study are observation, interviews, questionnaires, and tests. The data analysis used is descriptive qualitative and descriptive quantitative. The results of this study are expert validity tests with very good qualifications in the category of 100% learning material content experts, 94.66% learning design experts, and 93.33% learning media experts. The results of the product trial on individual trials were 94.28%, and small group trials were 92.85% with very good qualifications. The results of the effectiveness test of the application of interactive learning multimedia with an average pre-test of 55.83 and an average post-test of 89.17. This study has implications for interactive learning multimedia being able to improve student learning outcomes with a contextual approach so that learning is more meaningful. It can be concluded that interactive learning multimedia with a contextual approach is stated to be valid and effective in improving learning outcomes in the subject of science for grade V Elementary School students.